Measurement of acoustic attenuation in South Pole ice - Abbasi, R.; Abdou, Y.; Abu-Zayyad, T.; Adams, J.; Aguilar, J.; Ahlers, M.; Andeen, K.; Auffenberg, J.; Bai, X.; Baker, M.; Barwick, S.; Bay, R.; et al. (2011)
Using the South Pole Acoustic Test Setup (SPATS) and a retrievable transmitter deployed in holes drilled for the IceCube experiment, we have measured the attenuation of acoustic signals by South Pole ice at depths between 190 m and 500 m. Three data sets, using different acoustic sources, have been analyzed and give consistent results. The method with the smallest systematic uncertainties yields an amplitude attenuation coefficient α = 3.20 ± 0.57 km−1 between 10 and 30 kHz, considerably larger than previous theoretical estimates. Expressed as an attenuation length, the analyses give a consistent result for λ ≡ 1/α of ~300 m with 20% uncertainty. No significant depth or frequency dependence has been found.